The Effect of Iranian Identity Elements on the Soft Power of the Islamic Republic of Iran - Hossein Harsij; Mojtaba Tooyserkani (Taḥqīqāt-i Farhangī-i Īrān)
Soft power, is a product and result of positive portrait and credit achievement in the world public opinion, and indirectly affects other countries interests and behaviours, by utilization of such means as culture, brilliant backgrounds, and human ideals and values. Thus, soft power is a social phenomenon, related to environmental elements, that has been mostly influenced by elements of national identity, in contrast with other means of foreign policy. This study aimed at analyzing the impact degree of the foundations and elements of Iranian identity on the application of the soft power of the Islamic republic of Iran. In this direction, the current study, by making use of constructivist approach to comprehend national identity in Iran, has adopted descriptive method and based on analysis and argument.As the findings of this research indicate, among elements of national identity, a new Iranian identity, based on legal, human, as well as Islamic measures, in the framework of "religious democracy", has the main impact on the soft power of the Islamic Republic of Iran. Consequently, strengthening this element of Iranian identity leads to the utmost effectiveness of the soft power of the Islamic Republic of Iran in the world, and in the Muslim nations, in particular.